The buyer preferences on housing purchase decision at Perbadanan Kemajuan Negeri Selangor (PKNS) Shah Alam / Zahid Shuhadis - Shuhadis, Zahid (2008)
This paper studies the buyer preferences on housing purchase decision at Perbadanan Kemajuan Negeri Selangor (PKNS) Shah Alam. The analysis of variables will be analyzed to discover the buyer preferences on housing purchase decision. This research paper will use the independent and dependent variable to verify any relationship between the buyers and the preferences. Researcher will analyze the variables of place (location), product (house), house price, promotion and reason of purchase decision in the questionnaire. Besides questionnaire as the primary data, all the data were obtained from the secondary data. Journals and related information were obtained from internet and journals. The variables will be analyzed by using the frequency distribution, the reliability analysis, cross tabulation, the descriptive statistical analysis and lastly correlation analysis. Computer software of Statistical Package for Social Science (SPSS) is used in order to relate data and findings.